Effect of Brea Gum on the characteristics of wheat bread at different storage times. - López, Estela Patricia (2013)
The effect of Brea Gum (BG) addition on a basic bread formulation is described. The aim of the work was to study the effect of BG on the characteristics of wheat bread , analyzed in terms of variation in moisture, texture, retrogradation of amylopectin and microstructure. Bread quality was assessed by physical parameters (volume, specific volume index, width/height ratio, crumb moisture, color and hardness) and crumb grain structure (total cells number, total cells area, average size of cells and number of cells per unit area). The effect of BG on the characteristics of the crumb during storage for 24, 48 and 72 hours was determined through the change in moisture, hardness and amylopectin retrogradation. Furthermore, the microstructure of the crumb was analyzed by scanning electron microscopy (SEM). The results show the ability of BG to retain moisture in the bread crumb, which was expressed by the lower hardness of the bread crumbs with the hydrocolloid added at 48 and 72 hours of storage. This effect was also evident in the microstructure